Experimental Study on the Behaviour of Expansive Soils - Habibbeygi, Farzad (Curtin University, 2019)
In this research, laboratory-based experiments were conducted to investigate the volumetric and mechanical behaviour of expansive soils. The effects of clay mineralogy, initial water content and preconsolidation stress on the compressibility and shear strength of expansive clays were investigated. Predictive models based on regression analysis and artificial neural networks are proposed to estimate the compression and shear behaviour of expansive soils. Additionally, a green stabiliser was introduced to reduce the swell potential of expansive clays.